Time to Relapse and Relapse Predictors in Patients with Schizophrenia at Ayder Comprehensive Specialized Hospital, Northern Ethiopia - Habtamu Endashaw Hareru; Kebede Embaye Gezae; Daniel Sisay W/tsadik; Gebremedhin Berhe Gebregergs (Mental Illness)
Background. Rehospitalization, treatment resistance, and impairment are all possible outcomes of a schizophrenia relapse, which has a severe impact on patients, families, and the healthcare system. However, little is known regarding the time to relapse and relapse predictors in Ethiopia and in the study settings. Therefore, the aim of this study was to determine the time to relapse and relapse predictors in patients with schizophrenia at Ayder Comprehensive Specialized Hospital, Northern Ethiopia. Methods. A retrospective cohort study was carried out among 273 schizophrenia patients discharged from Ayder Comprehensive and Specialty Hospital between January 2015 and January 2019. The data was taken from the patient’s medical record and was chosen using a systematic random sampling procedure. A standardized data collection checklist was employed. The survival experiences of participants were compiled using a life table. Both univariate and multivariate Cox regression models were used for variable selection. Finally, after confirming the model’s diagnosis and assumptions, factors with a p value of less than 0.05 were declared to be statistically significant predictors of schizophrenia relapse. Results. In this study, the incidence of relapse was 2.9 per 100 person-months (PMs) and the median time to relapse of 13 months (interquartile range: 6–23 months). Being divorced (AHR=2.50, 95% CI: 1.18-5.28), not adhering to treatment (AHR=5.7, 95% CI: 3.03-10.74), and substance abuse (AHR=1.8, 95% CI: 1.01-3.22) were risk factors for increasing schizophrenia relapse. Age (AHR=0.65, 95% CI: 0.34-0.88) and length of first hospitalization (AHR=0.69, 95% CI: 0.57-0.86) were factors that decreased schizophrenia relapse. Conclusion and Recommendation. In this study, out of 100 patients with schizophrenia followed up for a month, three had a relapse, and the highest risk factor for relapse was treatment nonadherence, followed by being divorced and substance misuse. As a result, it is advised that all parties involved focus on early detection and taking preventive measures against schizophrenia relapse, as well as providing regular psychoeducation about the significance of treatment adherence and connecting patients with substance misuse to substance rehabilitation centers.